2012
DOI: 10.1002/etc.1759
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of two Cylindrospermopsis raciborskii (cyanobacteria) strains to mice, Daphnia, and fish

Abstract: In recent decades, toxic cyanobacterial blooms have become frequent in the drinking water supply and have caused serious deleterious effects to domestic and wild animals, as well as to humans. Two strains of the cyanobacterium species Cylindrospermopsis raciborskii (T2 and T3) were isolated from the Billings Reservoir (São Paulo, Brazil) and cultured in the laboratory for use in acute toxicity tests with mice, micro crustaceans, and fish. The results showed high toxicity of both strains in mouse bioassays (med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Although this hypothesis has been mainly directed toward microcystins and much of the research to date has been dedicated to this toxin, some evidence also points to strong grazerimpairing effects of other toxins, such as STX [15,16]. The aim of the present study was to test the hypothesis that natural water samples containing different classes of cyanotoxins as well as an STX-producing strain of C. raciborskii, isolated from the same reservoir, affect the swimming activity of 2 Daphnia species: D. pulex and D. similis, both previously known to be sensitive to STX-producing C. raciborskii strains [15,16,35]. To test this hypothesis, we used 2 approaches: 1) acute toxicity bioassays specially designed to detect the effects of neurotoxins [16], and 2) behavioral assays using an automated movement tracking system, which is able to track and measure continuously the swimming activity parameters of Daphnia.…”
Section: Introductionmentioning
confidence: 99%
“…Although this hypothesis has been mainly directed toward microcystins and much of the research to date has been dedicated to this toxin, some evidence also points to strong grazerimpairing effects of other toxins, such as STX [15,16]. The aim of the present study was to test the hypothesis that natural water samples containing different classes of cyanotoxins as well as an STX-producing strain of C. raciborskii, isolated from the same reservoir, affect the swimming activity of 2 Daphnia species: D. pulex and D. similis, both previously known to be sensitive to STX-producing C. raciborskii strains [15,16,35]. To test this hypothesis, we used 2 approaches: 1) acute toxicity bioassays specially designed to detect the effects of neurotoxins [16], and 2) behavioral assays using an automated movement tracking system, which is able to track and measure continuously the swimming activity parameters of Daphnia.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kaebernick and Neilan (2001) Saxitoxins are also known as paralytic shellfish toxins (PSTs) or poisons (PSPs) (Zagatto et al, 2012). These alkaloids are a group of neurotoxin carbamates that inhibit the propagation of nerve impulses in mammals through the blockage of sodium channels, which causes neuromuscular paralysis (Chorus and Bartram, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In acute tests with strain CYRF-01 (non-published data), D. rerio was not sensitive to concentrations as high as 5×10 5 cells ml -1 of intact cells and to 100 mg l -1 of lyophilized cell extracts. Zagatto et al [37], on the other hand, showed that D. rerio fish larvae were senstitive to two other STXs-producer strains of C. racibosrskii in chronic exposures (7 days). Therefore, these data show that fish larvae seem to be more sensitive to toxins produced by C. raciborskii than adult fish.…”
Section: Discussionmentioning
confidence: 99%